Long non‐coding RNA AFAP1‐AS1/miR‐320a/RBPJ axis regulates laryngeal carcinoma cell stemness and chemoresistance. Issue 9 (4th July 2018) - Yuan, Zhennan; Xiu, Cheng; Song, Kaibin; Pei, Rong; Miao, Susheng; Mao, Xionghui; Sun, Ji; Jia, Shenshan
Abstract: AFAP1‐AS1 is a long non‐coding RNA that is associated with tumorigenesis and poor prognosis in a variety of cancers. We have been suggested that AFAP1‐AS1 increases tumorigenesis in laryngeal carcinoma specifically by enhancing stemness and chemoresistance. We assessed AFAP1‐AS1 expression in human laryngeal specimens, paired adjacent normal tissues and human HEp‐2 cells. Indeed, we found not only that AFAP1‐AS1 was up‐regulated in laryngeal carcinoma specimens and cells, but also that stemness‐associated genes were overexpressed. Silencing of AFAP1‐AS1 promoted HEp‐2 cell chemoresistance under cisplatin treatment. Expression of AFAP1‐AS1 was increased in drug‐resistant Hep‐2 cells. We then probed the mechanism of AFAP1‐AS1 activity and determined that miR‐320a was a potential molecular target of AFAP1‐AS1. Luciferase reporter and qRT‐PCR assays of AFAP1‐AS1 and miR‐320a levels in human specimens and cell cultures indicated that AFAP1‐AS1 negatively regulates miR‐320a. To discover the molecular mechanism of miR‐320a, we again used the DIANA Tools algorithm to predict its genetic target, RBPJ. After cloning the 3′‐untranslated regions (3′‐UTR) of RBPJ into a luciferase reporter, we determined that miR‐320a did in fact reduce RBPJ mRNA and protein levels. Ultimately, we determined that AFAP1‐AS1 increases RBPJ expression by negatively regulating miR‐320a and RBPJ overexpression rescues stemness and chemoresistance inhibited by AFAP1‐AS1 silencing. Taken together, these results suggest that AFAP1‐AS1 can serve as a prognostic biomarker in laryngeal carcinoma and that miR‐320a has the potential to improve standard therapeutic approaches to the disease, especially for cases in which cancer cell stemness and drug resistance present significant barriers to effective treatment.